The evaluation of e-learning readiness as a distance learning media of the first-semester biology students - Ariandi Ariandi; Masyitha Wahid (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Universitas Sulawesi Barat (Unsulbar) launched its primary Learning Management System (LMS) named E-learning of Universitas Sulawesi Barat or often called “E-learning Unsulbar” in 2020 (https://elearning.unsulbar.ac.id/). Implementing E-learning at Unsulbar is one of the university’s efforts to maximize distance learning, especially during the COVID-19 pandemic. A study was conducted to evaluate E-learning readiness to measure the readiness of new students of the Biology Education Study Program towards the E-learning implementation. It is a quantitative descriptive study using a survey method adapted from a questionnaire developed by Akaslan and Law. The respondents were 77 new students from the biology education class of 2020 in the odd semester of 2020-2021. The measurement adapts three main stages, i.e., readiness (technology, people, institutions, content), acceptance, and training. The result showed that the readiness of new students for E-learning Unsulbar for technology and training factors were 3.1 and 3.3, respectively. It was categorized as not ready, which means that there needed to be more readiness of students’ internet infrastructures and academics who need training in using E-learning Unsulbar. Meanwhile, the scores for the factor of people, institutions, content, and acceptance were 3.8, 4.2, 3.85, and 3.9, respectively, and categorized as ready to be implemented. This result is an evaluation material for the university in determining the right policy for implementing E-learning Unsulbar.